2017
DOI: 10.1186/s41110-017-0040-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profile and gastroprotective potential of Myrcianthes pungens fruits and leaves

Abstract: Background: The last decade has been marked by increasing data regarding gastroinstestinal diseases, specially gastritis and ulcer. In order to prevent or treat these diseases, many studies have demonstrated the potential of medicinal plants. The aim of this study was to evaluate the phytochemical profile and the gastroprotective activity of the methanolic extract of Myrcianthes pungens whole fruit, peel, pulp, seeds, and leaves. Methods: The methanolic extracts were analyzed by thin layer chromatography (TLC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…floribunda was found to contain secondary metabolites such as flavonoids, alkaloids, terpenoids, fatty acids, and saponins among others. This agrees with earlier reports on the plant [ 16 , 39 ], which suggests that flavonoids and phenolic compounds possess good antiulcer and anti-inflammatory properties alongside other phytochemicals [ 33 , 40 ]. It is suggested that the presence of those phytochemicals contributed to the amelioration of gastric ulcers induced by ethanol administration.…”
Section: Discussionsupporting
confidence: 93%
“…floribunda was found to contain secondary metabolites such as flavonoids, alkaloids, terpenoids, fatty acids, and saponins among others. This agrees with earlier reports on the plant [ 16 , 39 ], which suggests that flavonoids and phenolic compounds possess good antiulcer and anti-inflammatory properties alongside other phytochemicals [ 33 , 40 ]. It is suggested that the presence of those phytochemicals contributed to the amelioration of gastric ulcers induced by ethanol administration.…”
Section: Discussionsupporting
confidence: 93%
“…The fruit is highly perishable, with a maximum shelf life of 3 days (73) , because it is extremely fragile in structure, requiring special care in the harvest (4) . Freeze-drying or freezing the pulp are options for its conservation that enable the maintenance of most bioactive compounds (74) , especially anthocyanins, phenolic compounds and carotenoids (75) . The concentration of anthocyanins increases during storage at room temperature (25 ºC) (75) .…”
Section: Guabiju [Myrcianthes Pungens Berg]mentioning
confidence: 99%